No more universities, please! - Abd Razak, Dzulkifli (2010)
LAST week, most dailies carried a picture of a girl handing a note to Prime Minister Datuk Seri Najib Razak expressing a desire for a university in her town. You cannot help but admire her for expressing her wants. And a university is not a bad choice either! She is not alone in this regard. Practically all states have at least one tertiary institution some have more than their fair share in proportion to their population. At one point, each state even wanted the person heading the institution to be its native as well. Fortunately, this request has run its course, but this does not detract from the fact that there are still demands for more higher education institutions.